Transcriptomic Changes in Response to Putrescine Production in Metabolically Engineered Corynebacterium glutamicum - Li, Zhen; Liu, Jian-Zhong (Frontiers in Microbiology, 2017)
Putrescine is widely used in industrial production of bioplastics, pharmaceuticals, agrochemicals, and surfactants. Although engineered Corynebacterium glutamicum has been successfully used to produce high levels of putrescine, the overall cellular physiological and metabolic changes caused by overproduction of putrescine remains unclear. To reveal the transcriptional changes that occur in response to putrescine production in an engineered C. glutamicum strain, a comparative transcriptomic analysis was carried out. Overproduction of putrescine resulted in transcriptional downregulation of genes involved in glycolysis; the TCA cycle, pyruvate degradation, biosynthesis of some amino acids, oxidative phosphorylation; vitamin biosynthesis (thiamine and vitamin 6), metabolism of purine, pyrimidine and sulfur, and ATP-, NAD- and NADPH-consuming enzymes. The transcriptional levels of genes involved in ornithine biosynthesis and NADPH-forming related enzymes were significantly upregulated in the putrescine producing C. glutamicum strain PUT-ALE. Comparative transcriptomic analysis provided some genetic modification strategies to further improve putrescine production. Repressing ATP- and NADPH-consuming enzyme coding gene expression via CRISPRi enhanced putrescine production.